Recommendations for Management of Diabetes During Ramadan - Monira Alarouj; R Bouguerra; John B. Buse; Sherif Hafez; Mohamed Hassanein; Mahmoud Ibrahim; Faramarz Ismail‐Beigi; Imad M. El‐Kebbi; Oussama Khatib; Suhail Kishawi; Abdulrazzaq Al-Madani; Aly A. Misha'l; et al. (2005)
It is estimated that there are 1.1–1.5 billion Muslims worldwide, comprising 18–25% of the world population (1,2). Fasting during Ramadan, a holy month of Islam, is an obligatory duty for all healthy adult Muslims. An ∼4.6% prevalence of diabetes worldwide (3) coupled with the results of the population-based Epidemiology of Diabetes and Ramadan 1422/2001 (EPIDIAR) study, which showed (in 12,243 people with diabetes from 13 Islamic countries) that ∼43% of patients with type 1 diabetes and ∼79% of patients with type 2 diabetes fast during Ramadan (4), lead to the estimation that some 40–50 million people with diabetes worldwide fast during Ramadan.